Characterization of Mother-Infant Relationship in Wild Geoffroy’s Spider Monkeys (Ateles geoffroyi) (2017)
Mother-infant relationships are essential from a development perspective and are particularly relevant in primates as they have a very prolonged period of development. Investigations of primate development have focused primarily on only a few species, with specific social systems and life histories, therefore it is important to extend developmental studies to other primates to have a precise and complete understanding of this phenomenon . I studied mother - infant relationships in Geoffroy’s spider monkey ( Ateles geoffroyi ), a New World monkey in danger of extinction that lives in multi - male/multi - female groups of 20 to 50 individuals that fission and fusion into subgroups varying in membership throughout a day. This implies that the infants interact with different members of the group depending on their mother’s subgroup, whic h could have important effects o n their behavioral development, especially in their socialization process. In addition, spider monkeys are an interesting model to study mother - infant relationships because of their exceptional slow developmental period, compared with other primates of similar size, which suggests that the quality of the relationship could be very important in the development of behavioral patterns. I conducted the rese arch i n the protected area of Otoch Ma’ax Yetel Kooh, located in the Yucatan peninsula, Mexico, with a group of monkeys that has been studied continuously since 1997. I focused on 12 dyads composed by all the infants of the group which were ≤3 years and their mothers. I used 15 - min focal sampling and 20 min scan sampling, with an ethogram of 37 measures associated with mother - infant interaction and infant independent behavior. Data collection was carried out from August 2016 to April 2017 . I collected 655 focal observations that covered 149.64 observation hours and 1,069 scans within approximately 770 hours of field work. Data w ere analyzed with R versio n 3.4 . 0 , using lineal mixed models, in which I included age as the predictive variable, an d group tenure of the mothers, and sex of the infants as control variables. Age had a significant effect ( p ≤.05) over a variety of measures of mother - infant relationship and infant behavior. The distance between mothers and infants , and the proportion of time in exploration and social proximity increased with age. Also, independent locomotion increased from 9 to 19 months of age, which was followed by a peak o n the rate of bridges around 20 months of age . Social play also reached a peak about this age . T hus, t wo crucial periods of independence were found before the first and the second years of age . T h e study s how ed that mother - infant relationships in wild spider monkeys are characterized by extended and slow periods of dependency and behavioral development when compare to primate species of similar or greater size . This was interpreted in the light of the diffe rent hypotheses that have been proposed to explain slow life histories. Finally , a gradual and soft transition toward infant independence was identified in the mother - infant dyads of the study , which was analyzed in the context of the risk that the ecologi cal and social characteristics of the species could represent to the infant.